Secret of the wings [videorecording (DVD)] - Whitman, Mae, 1988-; Hale, Lucy, 1989-; Bartys, Angela (Walt Disney Studios Home Entertainment, 2012)
Journey with Tinker Bell and her fairy friends into the forbidden world of the mysterious Winter Woods, where curiosity and adventure lead Tink to an amazing discovery and reveal a magical secret that could change her world forever.